2008
DOI: 10.1177/097324700800400109
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of Indian Companies – An Analytical Perspective

Abstract: This research paper focuses on an analytical valuation perspective of Indian companies. Five top companies from each of these sectors were selected on the basis of cumulative sales in the last ten-year period (1997–2006). These five top companies in each sector were selected from the total sample of 8500 companies. The companies were valued on the basis of eight financial parameters. The IT sector and infrastructure sectors have the highest average sales growth rate with three companies from each sector figuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This review has established that Tobin's Q is the most popularly used value-based performance measure (Gugler et al , 2008; Kumar and Suhas, 2008; Chauhan et al , 2016; Wei et al , 2005; Gunasekarage et al , 2007; Kohlbeck and Mayhew, 2010; Endri and Fathony, 2020) along with EVA, MVA, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This review has established that Tobin's Q is the most popularly used value-based performance measure (Gugler et al , 2008; Kumar and Suhas, 2008; Chauhan et al , 2016; Wei et al , 2005; Gunasekarage et al , 2007; Kohlbeck and Mayhew, 2010; Endri and Fathony, 2020) along with EVA, MVA, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, it is assumed that firms of the peer group behave almost similarly in an industry and their valuation should have similar base. Hence, the total MCAP, which is about the number of shares outstanding at a given time multiplied by market price can be considered as true firm value (Kumar and Suhas, 2008; Vélez-Pareja and Magni, 2009; Kohlbeck and Mayhew, 2010; Liow, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To know the effect and implications of IFRS, Anubha Srivastava (2020) attempts to study the differences between IGAAP and IFRS and found out that IFRS will reduce equity costs and frauds. Some studies revealed that the firsttime adoption of IND AS in the IT companies has no significant difference in the profitability due to transition (Kumar & Agarwal, 2020). Another side Teena Thomas and Tomy Mathew (2019) found out in their study that there is a significant difference in debtequity ratios on implementation of IGAAP and IND AS in energy sector.…”
Section: Review Of Literaturementioning
confidence: 99%